Terrible Olympias. Another Study in Method - Borja Antela (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2020)
Olympias of Epirus is one of the main characters in the history of the emergency of Macedonia as an international power with Philip II and Alexander. Nevertheless, despite the many books, papers and studies that had been improving our knowledge about Argead Macedonia in times of the great Macedonian conquerors, the historians of the XIXth and XXth centuries treated Olympias in the same terms of the ancient sources. This uncritical perspective denotes a clear tendency and aims to reproduce gender stereotypes that comes to our own days.